WEB NEWS SOURCES - BLASER, ART (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Several general news sources will occasionally have excellent reports on disability issues. The bad news is that the good ones will disappear; for instance most CSPAN excerpts disappear after only fifteen days in the archives. The good news is that even better ones will often replace them. The descriptions are generally those used on the websites.